Global innovation and entrepreneurship : challenges and experiences from East and West - Little, Stephen E., 1948-; Go, Frank M.; Poon, Teresa Shuk-Ching (Springer Nature, 2017)
Addressing the wide-ranging challenges of global entrepreneurship and innovation faced by both East and West, this edited volume provides a multi-faceted overview of the complexity facing entrepreneurial firms within global value chains. Viewed from the context of an emerging multi-polar world in which Europe and Asia are seen as major actors, the book explores their relations which are becoming increasingly crucial for the understanding of global politics, trade, technology, culture and travel. Global Innovation and Entrepreneurship includes case studies and discussions from a range of sectors and takes a unique cross-disciplinary perspective from European as well as East and South Asian authors.
Keywords: Business.; Entrepreneurship.; Management.; Industrial management.; International business enterprises.; International economic relations.; elektronické knihy; electronic books